Speciation of coagulase negative staphylococci, isolated from indoor air, using SDS page gel bands of expressed proteins followed by MALDI TOF MS and MALDI TOF-TOF MS-MS analysis of tryptic peptides - Fox, Karen; Fox, Alvin; Rose, John; Walla, Michael (Journal of microbiological methods, 2011)
A group of coagulase negative staphylococcal strains isolated from indoor air of occupied school rooms were the subject of this study. Conventional MALDI TOF MS profiling of cellular extracts and physiological tests (including API STAPH) provided incomplete identification of the set of strains. After separation of a 100 kDa band using 1D gel electrophoresis, profiling of peptides (released with tryptic digestion) using MALDI TOF MS allowed improved bacterial speciation in addition to determination of the identity of the protein of origin (aconitate hydratase). This was performed by Mascot search, empirical observation and computer-generated cross-correlation analysis of environmental isolates versus reference strains. The species studied included some with sequenced genomes and others with un-sequenced genomes. Peptide sequences were confirmed to originate from aconitate hydratase using MALDI TOF-TOF MS-MS analysis of a diverse set of m/ z values representing variable and conserved sequences. The methodological approach described here might have widespread application in speciation of environmental isolates of diverse origin and in identification of their expressed proteins. ► One of the first mass spectrometry works defining peptide markers for bacteria. ► May have widespread application in speciation of isolates of diverse origin. ► Profiling of tryptic peptides from gel bands allowed ready speciation. ► Cross-correlation of data from unknown and reference organisms aids identification. ► Proteins from species with sequenced or un-sequenced genomes can be compared.